Mediator - enabler for successful digital health care - Janne Lahtiranta (Finnish Social and Health Informatics Association, 2017)
It is no news that as in any other field of industry, digitalization is changing health care. This change is ongoing and profound as it affects every aspect imaginable; from provisioning to funding, and from roles to responsibilities. The magnitude of this change is such that some label it as the 'health care revolution'. Not all individuals are ready for this 'revolution'. Some rebel against it while others are simply not able to cope with it. Regardless of the underlying reason, it can be estimated that in the near future, roughly 10 % of the population in the OECD countries will drift outside the reach of the modern electronic health care services. These individuals, the digital orphan, need to be brought back in order to prevent the future of health care from becoming more marginalized and discriminatory than it is today. Mediators, individuals in the crux of health care and technology, are one way to prevent this unwelcome eventuality from coming true. In the following, the focus of examination is on the mediators and mediation. The role of a mediator is critically examined from different perspectives, and a framework for mediation is presented.